2018
DOI: 10.18261/issn.1893-8981-2018-03-07
|View full text |Cite
|
Sign up to set email alerts
|

Kollegaveiledning i høyere utdanning

Abstract: Peer mentoring between professionals is based on the idea that professional employees at the same level collaborate by giving each other feedback without support from an external super-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Bell & Mladenovic, 2008;M. Bell & Cooper, 2013;Buchanan & Parry, 2019;Bulman et al, 2016;Byrne et al, 2010;Carroll & O'Loughlin, 2014;Davis, 2011;de Lange & Lauvås, 2018;Deni & Malakolunthu, 2013;Hammersley-Fletcher & Orsmond, 2004, 2005Kell & Annetts, 2009;O'Keefe et al, 2009;Quinlan & Åkerlind, 2000;Servilio et al, 2017;Shortland, 2010;Shousha, 2015;Thampy et al, 2015;Torres et al, 2017;Wildman et al, 2000;Wingrove et al, 2015;Wingrove et al, 2018;Yiend et al, 2014 Group size Pairs (20) A. Bell & Mladenovic, 2015;…”
Section: Factors That Shape Collegial Faculty Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Bell & Mladenovic, 2008;M. Bell & Cooper, 2013;Buchanan & Parry, 2019;Bulman et al, 2016;Byrne et al, 2010;Carroll & O'Loughlin, 2014;Davis, 2011;de Lange & Lauvås, 2018;Deni & Malakolunthu, 2013;Hammersley-Fletcher & Orsmond, 2004, 2005Kell & Annetts, 2009;O'Keefe et al, 2009;Quinlan & Åkerlind, 2000;Servilio et al, 2017;Shortland, 2010;Shousha, 2015;Thampy et al, 2015;Torres et al, 2017;Wildman et al, 2000;Wingrove et al, 2015;Wingrove et al, 2018;Yiend et al, 2014 Group size Pairs (20) A. Bell & Mladenovic, 2015;…”
Section: Factors That Shape Collegial Faculty Developmentmentioning
confidence: 99%
“…These tools are considered part of the context, as they are developed as part of the common practices in the given institution or discipline and therefore incorporate the norms, knowledge, and values of the given context. Specific sets of rules and guidelines for how to give feedback and what to assess during observation situations were perceived as helpful in keeping effective time and maintaining a focus on the pedagogical side of the problems (de Lange & Lauvås, 2018;de Lange & Wittek, 2018;Torres et al, 2017). Others reported that formalizing the CFD process created a more stressful environment that impeded their freedom (Hammersley-Fletcher & Orsmond, 2004).…”
Section: Rules and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…I forskningslitteraturen finnes det dokumentasjon for at systematisk arbeid med kollegaveiledning har et stort potensiale til å bidra til økt profesjonalitet og bedre undervisning og veiledning (Esterhazy et.al., under publisering). Det å drøfte utfordringer i undervisningshverdagen med kolleger som man stoler på, er anbefalt som en effektiv tilnaerming for kvalitetsarbeid i høyere utdanning (Costa & Kallik, 1993;Kohut, Burnap, & Yon, 2007;Sachs & Parsell, 2013), og det anbefales gjerne å benytte en bestemt metode for å skape en forutsigbar og fokusert innramming (de Lange og Lauvås 2018;Thomas et al, 2014). Når profesjonsutøvere fra ulike miljøer møtes for å samarbeide, bidrar det til at ekspertise distribueres (Edwards 2005(Edwards , 2011de Lange & Wittek, 2018).…”
Section: Tidligere Forskning Om Kollegaveiledningunclassified
“…Veiledningssamtalene kan dermed fremkomme som en systematisk, faglig og personlig laereprosess for studentene, innenfor en anerkjennende og støttende ramme (Høium & Tørris, 2018). Struktur viser seg også å vaere avgjørende for å kunne holde fokus på den andre og holde seg til hjelperrollen uten å vaere eksperten om tar over (de Lange & Lauvås, 2018).…”
Section: Diskusjonunclassified